Investigating community relations among residents in the village of Tanah Merah, North Jakarta - Herawati, H.; Abubakar , Akhmad H. (Journal of Community Service and Empowerment, 2024)
This study examines the relationship among residents in the community of Kampung Tanah Merah, North Jakarta, with a focus on their social dynamics, aspirations and interactions. The community in this area faces various challenges such as inadequate infrastructure, and limitations in economy and education. This study aims to understand how residents organize themselves and participate in decision-making that affects their lives, and how they voice their aspirations and hopes for improved welfare. The methods used include semi-structured interviews, participant observation and document studies. The results of the study indicate that the community has a strong social structure with active local leadership, but still faces difficulties in accessing government programs. This study concludes that improving relation between residents and the government and other parties is essential to achieving better welfare. These findings are expected to provide policy recommendations that support inclusiveness and active participation of residents in the development of their environment.